Long-Circulating Liposomal Delivery System Targeting at PDGFR-β Enhances the Therapeutic Effect of IFN-α on Hepatic Fibrosis - Li, Qinghua; Yu, Qi; Ju, Jing; You, Tiangeng; Yan, Zhiqiang; Nan, Xiangli; Zhong, Jie; Zhou, Jing E (Current pharmaceutical design, 2017)
In this study, we developed a drug of IFN-α combined with pPB-SSLs, which specifically target at platelet-derived growth factor receptor-β (PDGFR-β). The aim of this study is to improve the limitations of IFN-α including insufficient drug concentration for the target cells and side-effects causing serious concerns in treatment of hepatic fibrosis. We constructed the targeted stable liposomes (SSLs) that not only increase the half-life period of IFN- α, but also can deliver IFN-α to hepatic stellate cells (HSCs). Subsequently, the anti-hepatic-fibrosis effect of pPB-SSL-IFN-α was evaluated both in vitro and in vivo. Immunofluorescent assay showed that the pPB-SSL particles were able to be easily taken up by 3T3 cells. The cellular distribution experiment demonstrated that most of the pPB-SSL-IFN-α would accumulate around the fibroblast, and the cell would be invaded by pPB-SSLIFN- α. The pPB-SSL-IFN-α showed an entrapment efficiency of 39.73 ± 5.21% for IFN-α and the particles reached nanoscale level. It showed more significant alleviated performance for hepatic fibrosis than IFN-α. Both in vitro and in vivo, the pPB-SSL-IFN-α could contribute to reduction or inhibition in the expression of TGF-β1 and α-SMA even cleavage of caspase-3. Moreover, it was found that the pPB-SSL-IFN-α induced the apoptosis of 3T3 cells by inhibiting the expression of TGF-β1 as well as α-SMA. Under observation for fibrotic liver of mice treated with pPB-SSL-IFN-α, the semiquantitative score for collagen I, TGF-β1 and α-SMA were all inferior to the control group and those treated with PEG-IFN-α, SSL-IFN-α or IFN-α. In addition, pPB-SSL-IFN-α has been detected to down-regulate the expression of TNF-α and IL-1β in comparison with model group (P<0.01). And the phosphorylations of JAK1 and STAT1 were enhanced by pPB-SSL-IFN-αin comparison with model groups (P < 0.01). All results of our present research indicated that the pPB-SSL-IFN-α might be an alternative antiliver fibrotic drug and the synthetic method may offer a new access to the anti-hepatic fibrosis research and development.